Spatio-Temporal Declines in Philippine Fisheries and its Implications to Coastal Municipal Fishers' Catch and Income - Anticamara, Jonathan A.; Go, Kevin T. B. (Frontiers in Marine Science, 2016)
The problem of overexploitation in global fisheries is well-recognized. However, published assessment of fisheries spatio-temporal trends at the national scale is lacking for many high biodiversity developing countries, which is problematic since fisheries management is often implemented at the local or national levels. Here, we present the long-term spatio-temporal trends of Philippine fisheries production based on the landed national fish catch data (1980–2012) and fishers' interviews. We found that the total Philippine fish catch volume (Metric Tons MT) of most capture fisheries throughout the country has either stagnated or declined over the last three decades. The decline is even more prominent when evaluating fisheries trends at the provincial level, suggesting spatial serial depletion of the country's fisheries. In contrast, the total Philippine fish catch value (US Dollars US or Philippine Pesos PHP) has continued to increase over time, despite the declining fish catch volume. However, local municipal fishers are experiencing both low fish catch and income, contributing to observable poverty in many coastal communities in the Philippines. The various stakeholders of Philippine fisheries need to recognize the depleted state of Philippine fisheries, and learn from various experiences of collapsed and recovered fisheries from around the world, in order to recover the Philippines' capture fisheries. Lessons from the literature on collapsed fisheries offer the following options for recovery: (1) regulate or reduce fisheries exploitation and other human activities impacting the fisheries to allow fisheries to rebuild or recover, (2) enforce effective networks of marine reserves, (3) engage fishers, consumers, and other stakeholders in fisheries management, (4) improve fisheries science, monitoring, and management capacities, and (5) provide alternative livelihood, skills, and improved education to fishers and their families.